Videnskab og hverdagssprog. Grundtvigs betragtning af modersmålet i teori og praksis, belyst ved hans afhandling Om Ordsprog - Schmidt, Bodil (Grundtvig-studier, 1980)
Science and everyday language. Grundtvig’s View of his Native Tongue in Theory and in Practice. As Illustrated by his Article - Om Ordsprog (On Proverbs) 1817 By Bodil Schmidt Preserved in the Grundtvig archives are several collections in Grundtvig’s own handwriting of proverbs and popular sayings. In his magazine - Dannevirke - he argued for the preservation of this treasure of Danish proverbs, and urged his readers to assist in their collection.In his demand for a strengthening of the native tongue, Grundtvig was at one with his contemporary romantic poets and philosophers. His article argues for the originality of the Danish language and at the same time protests against the theories that it descends from Icelandic or German. Since his aim is practical, Grundtvig’s article is written in a less philosophical and polemical language than most of the other articles in the magazine. After a lengthy introduction criticising the position of poetry in the 18th century, Grundtvig defines the concept of “proverb” and lists the areas in which proverbs are of importance: language, morals, poetry, history. He follows this with a detailed guide as to how they could be collected. He makes the point, amongst others, that proverbs are useful in the translation of the ancient chronicles of Saxo and Snorre, which he was currently working on. He declares that the aim of his scientific efforts was to protect and enrich the Danish language so that it was qualified to re-awaken the Danish national spirit.A comparison of certain quotations with the common themes of Grundtvig and his colleague in the field, Christian Molbech, shows a marked difference in linguistic style. Where Grundtvig’s language is living, popular and concrete, Molbech’s is academic, stiff and abstract. The quotations included also reveal a decisive difference in the two writers’ view of the people and in their understanding of what the spirit of the people (folkelighed) actually is. Molbech regards “the rough peasant” as a natural creature with no real consciousness and therefore one whom there is no point in trying to enlighten, whereas Grundtvig believes that though the people may be idle and apathetic, they can and must be re-awakened.According to the author of the article there is a parallel between Grundtvig’s attack on the contemporary language of philosophy and our current debate on language being defined politically or ideologically. For Grundtvig, it was obvious that whoever wishes to be understood should use clear and unambiguous language, as close to everyday language as possible. The author asks why, in spite of the advances of science, democratic Denmark should accept that contemporary philosophers, theologians, sociologists and humanists employ a language that we only half understand. Do the Danes still doubt their basic common sense to distinguish between what is true and false? She quotes the proverb: All that glitters is not gold.